Knowledge and practice of essential newborn care among rural mothers - Begum, Mst Beauty; Mittra, China Rani; Shaha, Ashees Kumar; Mondal, Priti Lata; Naher, Kamarun; Halim, Kazi Shafiqul (Asian Journal of Medical and Biological Research, 2021)
Components of essential newborn care (ENC) and neonatal resuscitation are proven interventions for reducing neonatal mortality rate and stillbirth rates. This cross-sectional study was carried out among 354 rural mothers to assess the level of knowledge and practice of ENC. The study was conducted from 1st January to 31st December 2019 in Panchagarh district. Rural mothers were interviewed with a semi-structured pre-tested questionnaire and an observational check list was also used. This study revealed that, majority of the respondents 306 (86.4%) knew that baby should be kept warmth by wrapping with dry cloth and 39(11.0%) respondents should be kept in skin to skin contact immediately after delivery to maintain thermoregulation. From the total respondents 202 (57.1 %) knew that once should start breast feeding immediately after birth. Out of 354 respondents 344 (97.2%) gave colostrum to their baby. The study also finds that, 210 (59.3%) respondents had inadequate knowledge regarding essential new born care while 144 (40.7%) had adequate knowledge and 164 (46.3%) respondents had inadequate practice regarding essential new born care while 190 (53.7%) had adequate practice. Respondents who had inadequate knowledge had significantly more inadequate practice than others (p<0.001). Effective interventions can improve key newborn care practices, care-seeking and, in high mortality settings, reduce newborn mortality. Asian J. Med. Biol. Res. December 2020, 6(4): 785-794